But time and chance The story of Padre Martinez of, 1793-1867 - Chavez, Angelico (Sunstone Press Santa Fe, New Mexico, 1981)
I returned, and saw under the sun, that the race is not to the swift, nor the battle to the strong . . . but time and chance happenethto them all. Ecclesiastes 9:11 With these words, the epitaph Padre Martinez chose for himself, the reader is drawn into a stirring and provocative biography recounted by a master storyteller. Fray Angelico Chavez, articulate and well-versed in New Mexicana, vividly records the life of the controversial Padre of Taos so that the reader gains full measure of his surroundings and of the times. Martinez was continually at the forefront of the public and political forums . . . a master of jurisprudence and canon law . . . a champion of the underdog. With the advent of Bishop Lamy, public attention became focused on these two dynamic personalities. Their philosophic differences ultimately led to Martinez' suspension and excommunication. Chavez was a curious and indefatigable researcher and he used these talents well while delving into the facts and legends surrounding Padre Martinez most poignant and colorful life-drama . . . a personality to be reckoned with, whether as hero or villain, or both. Readers will, at once, share with Chavez his absorption in this man and, also wonder . . . how such a phenomenon could have sprouted and bloomed under the most adverse circumstances of time and place.
51076
Keywords: Martinez, Antonio Jose -- 1793-1867; Southwest; Catholic Church; Clergy; New Mexico